Zero alkali metal ion contamination ternary copolymer dispersant and preparation method and application thereof
Patent Information
- Application Number
- CN202610883381.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2046-06-18
AI Technical Summary
然而,钠盐类分散剂虽然分散效率高,但是微量的碱金属离子(Na+或K+)在高温烧结时会形成低熔点共晶物,破坏电子元器件的绝缘层,或在电池中导致严重的自放电现象,难以满足高纯电子浆料对离子污染控制的要求
①本发明在合成及后处理过程中采用非金属引发剂和有机溶剂体系,不引入碱金属元素,具有零离子污染的优势,所得产品灰分极低,完全满足MLCC及锂电池级别的纯度要求;经高温灰化法测试,实施例所得分散剂固体灰分≤0.015 wt%,经ICP-MS测试,Na+和K+含量均低于0.5 mg/kg。
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymeric surfactant technology, specifically to a terpolymer dispersant with zero alkali metal ion contamination, its preparation method, and its application. Background Technology
[0002] In the fields of high-end electronic pastes (such as MLCC nickel paste) and new energy battery pastes, dispersants play a crucial role in reducing viscosity, improving solidification, and stabilizing dispersion, acting as a powerful lever. Currently available commercial dispersants are mostly sodium or ammonium salts of polyacrylate. However, while sodium salt dispersants offer high dispersion efficiency, trace amounts of alkali metal ions (Na₂O₃) are present. + or K + During high-temperature sintering, low-melting-point eutectics can form, damaging the insulating layer of electronic components or causing severe self-discharge in batteries, making it difficult to meet the requirements for ion contamination control in high-purity electronic pastes. Although ammonium salt dispersants solve the problem of metal residue, they have a strong odor and are prone to causing drastic pH fluctuations during drying, which limits their widespread application.
[0003] In addition, although the styrene-maleic anhydride (SMA) system is a classic dispersant in electronic pastes, the reaction reactivity of styrene monomers varies greatly, resulting in uneven composition distribution. Furthermore, its excessive hydrophobicity leads to poor compatibility in polar conductive pastes, affecting the long-term storage stability of the paste. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a terpolymer dispersant with zero alkali metal ion contamination, its preparation method, and its application. The terpolymer dispersant provided by this invention possesses both high-efficiency dispersing ability and long-term storage stability under conditions without the introduction of metal ions.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a terpolymer dispersant with zero alkali metal ion pollution, which is obtained by copolymerizing itaconic acid monomer, benzyl methacrylate monomer and hydroxypropyl methacrylate monomer under the action of an initiator; The molar ratio of itaconic acid monomer, benzyl methacrylate monomer and hydroxypropyl methacrylate monomer is (1.0~2.0):(1.0~3.0):(0.5~1.5).
[0006] Preferably, the zero-alkali metal ion contamination terpolymer dispersant has a molecular weight distribution index of 1.5~2.5, a weight-average molecular weight of 5000~15000 g / mol, and an ash content ≤0.05wt% based on the solid content of the terpolymer dispersant, and a Na content of ≤0.05wt%. + Content ≤1.0 mg / kg, K+ Content ≤1.0 mg / kg.
[0007] Preferably, the zero-alkali metal ion contamination terpolymer dispersant exists in the form of free acid or organic amine salt.
[0008] Preferably, the initiator includes an organic peroxide or an azo initiator, wherein the organic peroxide or azo initiator does not contain alkali metal or alkaline earth metal ions.
[0009] This invention provides a method for preparing the above-mentioned terpolymer dispersant with zero alkali metal ion contamination, comprising the following steps: Benzyl methacrylate and hydroxypropyl methacrylate were mixed to obtain a monomer mixture; Itaconic acid, organic solvent and chain transfer agent are mixed to obtain the reaction precursor solution; The precursor solution is heated to the polymerization reaction temperature, and the monomer mixture and the first initiator solution are added dropwise simultaneously. The polymerization reaction is carried out simultaneously during the dropwise addition to obtain the polymerization reaction solution. A second initiator is added to the polymerization reaction solution to carry out a aging reaction, thereby obtaining a terpolymer dispersant with zero alkali metal ion contamination.
[0010] Preferably, the chain transfer agent comprises one or more of dodecyl mercaptoethanol, mercaptoethanol, isooctyl mercaptoacetate, isooctyl 3-mercaptopropionate, tert-dodecyl mercaptoethanol, and n-octyl mercaptoethanol; The chain transfer agent accounts for 0.05 to 0.8% of the total monomer mass.
[0011] Preferably, the mass of the first initiator is 0.5% to 1.5% of the total monomer mass; The mass of the second initiator is 0.05 to 0.5% of the total monomer mass.
[0012] Preferably, the polymerization reaction temperature is 75~85℃, and the synchronous dropwise addition time of the monomer mixture and the first initiator solution is 2~4h.
[0013] Preferably, the ripening reaction is carried out at a temperature of 85-95°C for 2-4 hours.
[0014] This invention provides the application of the above-mentioned zero-alkali metal ion contamination terpolymer dispersant in electronic pastes.
[0015] This invention provides a ternary copolymer dispersant with zero alkali metal ion contamination, obtained by copolymerizing itaconic acid monomer, benzyl methacrylate monomer, and hydroxypropyl methacrylate monomer under the action of an initiator; the molar ratio of itaconic acid monomer, benzyl methacrylate monomer, and hydroxypropyl methacrylate monomer is (1.0~2.0):(1.0~3.0):(0.5~1.5). This invention uses bio-based itaconic acid to replace traditional acrylic acid or maleic acid, utilizing its unique "methylene succinic acid" structure to provide high-density dicarboxyl anchoring points. Simultaneously, benzyl methacrylate is introduced to provide a more suitable π-π stacking adsorption energy for inorganic powders, and a steric hindrance layer is constructed in conjunction with long-chain hydroxypropyl methacrylate. Through the synergistic effect of monomer structure design and molecular weight control, this invention possesses a dual "electrostatic-steric" stabilization mechanism, achieving both high-efficiency dispersion and long-term storage stability under conditions without the introduction of metal ions.
[0016] Compared with the prior art, the present invention has the following beneficial effects: ① This invention uses a non-metallic initiator and organic solvent system in the synthesis and post-processing, without introducing alkali metal elements, thus having the advantage of zero ion contamination. The resulting product has extremely low ash content, fully meeting the purity requirements of MLCCs and lithium batteries. High-temperature ashing testing showed that the solid ash content of the dispersant obtained in the examples was ≤0.015 wt%, and ICP-MS testing showed that Na... + and K + The content was all below 0.5 mg / kg.
[0017] ② This invention uses a specific monomer ratio to achieve a balance between molecular weight and functional group distribution, which reduces the viscosity of the slurry and prevents coarsening during long-term storage.
[0018] ③ The dispersant of this invention is applicable to the internal electrode slurry of multilayer ceramic capacitors (MLCC), the positive electrode slurry of lithium-ion batteries, or nano-color pastes, and has good versatility.
[0019] This invention provides a method for preparing the above-mentioned terpolymer dispersant with zero alkali metal ion pollution. This method is simple to operate, low in cost, and easy to achieve industrial-scale mass production. Detailed Implementation
[0020] This invention provides a terpolymer dispersant with zero alkali metal ion pollution, which is obtained by copolymerizing itaconic acid monomer, benzyl methacrylate monomer and hydroxypropyl methacrylate monomer under the action of an initiator; The molar ratio of itaconic acid monomer, benzyl methacrylate monomer, and hydroxypropyl methacrylate monomer is (1.0~2.0):(1.0~3.0):(0.5~1.5), preferably (1.0~1.5):(1.0~2.0):(0.5~1), and specifically can be 1:1:1, 1.5:1:0.5, 1.5:1:1, 1:1.5:1, 1:2:1, or 1:1:1.5.
[0021] In this invention, the itaconic acid has a special β-carboxyl group structure, which has a stronger chelating ability on the surface of metal oxides compared with ordinary acrylic acid, and has a strong anchoring effect. Moreover, itaconic acid itself does not contain any metal ions and will not cause alkali metal ion pollution.
[0022] In this invention, the hydroxypropyl methacrylate serves to construct a solvation protective layer and enhance steric hindrance. Compared to hydroxyethyl, hydroxypropyl methacrylate has a longer side chain and a better extended conformation in organic media, thus forming a thicker solvation protective layer.
[0023] In this invention, benzyl methacrylate plays a compatibility regulating role. The benzyl methacrylate benzyl ring structure provides rigid support to prevent molecular chain curling, while having good affinity with carbon materials or metal surfaces.
[0024] In this invention, the initiator includes an organic peroxide or an azo initiator, wherein the organic peroxide or azo initiator does not contain alkali metal or alkaline earth metal ions; in this invention, the initiator is preferably one or more of benzoyl peroxide (BPO), di-tert-butyl peroxide (DTBP), and azobisisoheptanenitrile (ABVN).
[0025] In this invention, the molecular weight distribution index of the zero-alkali metal ion contamination terpolymer dispersant is preferably 1.5~2.5, more preferably 1.8~2.2, and even more preferably 2.0; the weight-average molecular weight of the terpolymer dispersant is preferably 5000~15000 g / mol, more preferably 8000~12000 g / mol, and even more preferably 10000 g / mol; in this invention, zero alkali metal ion contamination means that no alkali metal salt is actively introduced during synthesis, formulation, and post-treatment, and the Na content in the resulting dispersant solid is zero. + and K + The content is preferably ≤1.0 mg / kg, more preferably less than 0.5 mg / kg, and the ash content is preferably ≤0.05 wt%.
[0026] In this invention, the zero-alkali metal ion contamination terpolymer dispersant is preferably in the form of free acid or organic amine salt. The organic amine is preferably one or more of triethylamine, dimethylethanolamine and aminomethylpropanol. The neutralization method of the organic amine salt does not introduce alkali metal bases such as NaOH and KOH, thereby avoiding alkali metal ion residue.
[0027] This invention provides a method for preparing the above-mentioned terpolymer dispersant with zero alkali metal ion contamination, comprising the following steps: Benzyl methacrylate and hydroxypropyl methacrylate were mixed to obtain a monomer mixture; Itaconic acid, organic solvent and chain transfer agent are mixed to obtain the reaction precursor solution; The precursor solution is heated to the polymerization reaction temperature, and the monomer mixture and the first initiator solution are added dropwise simultaneously. The polymerization reaction is carried out simultaneously during the dropwise addition to obtain the polymerization reaction solution. A second initiator is added to the polymerization reaction solution to carry out a aging reaction, thereby obtaining a terpolymer dispersant with zero alkali metal ion contamination.
[0028] Unless otherwise specified, all raw materials used in this invention are commercially available.
[0029] This invention involves mixing benzyl methacrylate and hydroxypropyl methacrylate to obtain a monomer mixture. The mixing method is not particularly important; any method well-known to those skilled in the art, such as stirring, can be used.
[0030] This invention involves mixing itaconic acid, an organic solvent, and a chain transfer agent to obtain a reaction precursor solution. In this invention, the organic solvent is preferably one or more of propylene glycol methyl ether acetate (PMA), diethylene glycol butyl ether, and isopropanol or ethanol; the mass ratio of itaconic acid to the organic solvent is preferably 1:(2~5), more preferably 1:(2.5~3.5). In this invention, the chain transfer agent preferably includes one or more of dodecyl mercaptoethanol, mercaptoethanol, isooctyl mercaptoacetate, isooctyl 3-mercaptopropionate, tert-dodecyl mercaptoethanol, and n-octyl mercaptoethanol; the mass of the chain transfer agent is preferably 0.05~0.8% of the total monomer mass, more preferably 0.1~0.5%.
[0031] In this invention, the precursor solution is heated to the polymerization reaction temperature, and a monomer mixture and a first initiator solution are simultaneously added dropwise. The polymerization reaction occurs concurrently during the dropwise addition, resulting in a polymerization reaction solution. In this invention, the mass of the first initiator is preferably 0.5-1.5% of the total monomer mass, more preferably 0.8-1.0%; the solvent in the first initiator solution is preferably the same as the organic solvent in the precursor solution, and the mass concentration of the first initiator solution is preferably 1-5%, more preferably 2-4%.
[0032] In this invention, the polymerization reaction temperature is preferably 75-85°C, more preferably 80°C, and the simultaneous dropwise addition time of the monomer mixture and the first initiator solution is preferably 2-4 hours, more preferably 3 hours. By controlling the polymerization reaction temperature and the dropwise addition time of the monomers and initiator, this invention aims to maintain relatively stable instantaneous concentrations of itaconic acid, benzyl methacrylate, and hydroxypropyl methacrylate in the reaction system, reducing the risk of localized self-polymerization and compositional drift, thereby obtaining a terpolymer with uniform compositional distribution and a narrow molecular weight distribution.
[0033] This invention involves adding a second initiator to the polymerization reaction solution to conduct a ripening reaction, thereby obtaining a terpolymer dispersant with zero alkali metal ion contamination. In this invention, the mass of the second initiator is preferably 0.05-0.5% of the total monomer mass, more preferably 0.10-0.30%. In this invention, the ripening reaction temperature is preferably 85-95°C, more preferably 90°C, and the time is preferably 2-4 hours, more preferably 3 hours. This invention uses heating to carry out the ripening reaction, which further consumes residual monomers and improves the polymerization conversion rate, reduces the impact of unreacted monomers on the odor, volatile matter, and storage stability of the electronic paste, and avoids the use of alkali metal salt post-treatment agents.
[0034] After the aging reaction, the present invention preferably removes part of the solvent by distillation or dilution of the obtained aging reaction solution to adjust the solid content and obtain a terpolymer dispersion with zero alkali metal ion contamination. In the present invention, the solid content of the dispersion is preferably 30-60 wt%, more preferably 40-50 wt%.
[0035] This invention provides the application of the aforementioned zero-alkali metal ion contamination ternary copolymer dispersant in electronic pastes. In this invention, the electronic paste preferably includes an internal electrode paste for multilayer ceramic capacitors (MLCCs), a positive electrode paste for lithium-ion batteries, or a nano-color paste. In this invention, the dispersed inorganic powder preferably includes one or more of barium titanate, lithium iron phosphate, conductive carbon black, nickel powder, silver powder, alumina, zirconium oxide, silicon powder, carbon nanotubes, and graphene; the particle size of the inorganic powder is preferably 20 nm to 5 μm, more preferably 50 nm to 1 μm. In this invention, the dispersing solvent in the electronic paste is preferably one or more of N-methylpyrrolidone, butanone, ethanol, propylene glycol methyl ether acetate, terpineol, isopropanol, ethyl acetate, and diethylene glycol butyl ether; the solid content of the electronic paste is preferably 30 to 85 wt%, more preferably 50 to 75 wt%. In this invention, the mass of the solid terpolymer dispersant with zero alkali metal ion contamination is preferably 0.1-5% of the mass of the inorganic powder, more preferably 0.5-2%.
[0036] The following detailed description, in conjunction with embodiments, illustrates the zero-alkali metal ion contamination terpolymer dispersant provided by the present invention, its preparation method, and its application. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0037] Example 1: Balanced Dispersant (Standard Formulation) In this embodiment, the molar ratio of each monomer in the copolymer dispersant is IA:BzMA:HPMA = 1:1:1.
[0038] The preparation method of the terpolymer dispersant adopts the following steps: (1) In a four-necked flask equipped with a condenser and a mechanical stirrer, add 200g of propylene glycol methyl ether acetate (PMA), 65g (0.5mol) of itaconic acid (IA), and 0.5g of chain transfer agent dodecyl mercaptan. Purge with nitrogen and heat to 80°C to completely dissolve the itaconic acid.
[0039] (2) Mix 88g (0.5mol) of benzyl methacrylate (BzMA) and 72g (0.5mol) of hydroxypropyl methacrylate (HPMA) evenly. Separately dissolve 2.0g of the initiator azobisisoheptanenitrile (ABVN) in 50g of PMA.
[0040] (3) Keep the temperature at 80°C and add the monomer mixture and initiator solution dropwise into the flask simultaneously. The monomer is added over 3 hours and the initiator is added over 3.5 hours.
[0041] (4) After the addition is complete, the temperature is raised to 90°C, 0.5g of ABVN is added, and the mixture is kept warm for 3 hours. The mixture is then cooled and discharged to obtain a slightly yellow transparent terpolymer dispersion with a solid content of 45%.
[0042] Example 2: High-anchoring dispersant In this embodiment, the molar ratio of each monomer in the copolymer dispersant is IA:BzMA:HPMA = 1.5:1:0.5.
[0043] The steps are basically the same as in Example 1, except that the monomer feed amounts are adjusted to: itaconic acid 97.5g (0.75mol), benzyl methacrylate 88g (0.5mol), and hydroxypropyl methacrylate 36g (0.25mol).
[0044] This embodiment increases the density of anchoring groups, which is beneficial for nanopowders with extremely large specific surface areas.
[0045] Example 3: High steric hindrance dispersant In this embodiment, the molar ratio of each monomer in the copolymer dispersant is IA:BzMA:HPMA = 1:1:1.5.
[0046] The steps are basically the same as in Example 1, except that the monomer feed amounts are adjusted to: 65g (0.5mol) itaconic acid, 88g (0.5mol) benzyl methacrylate, and 108g (0.75mol) hydroxypropyl methacrylate.
[0047] This embodiment enhances the solvation layer thickness for systems prone to aggregation.
[0048] Comparative Example 1 This comparative example uses a traditional styrene-maleic anhydride (SMA) copolymer (molar ratio 1:1) with a weight-average molecular weight of 10,000 g / mol and no hydroxyl side chains.
[0049] Comparative Example 2 This comparative example uses commercially available sodium polyacrylate dispersant, manufactured by Nopcosperse Co., Ltd. of Japan, model Nopcosperse SN-5040 (containing Na). + ion).
[0050] Comparative Example 3 In Example 1, hydroxypropyl methacrylate (HPMA) was replaced with hydroxyethyl methacrylate (HEMA), while keeping all other conditions the same, to verify the effect of hydroxyl side chain length on steric hindrance and dispersion stability.
[0051] Comparative Example 4 In Example 1, benzyl methacrylate (BzMA) was replaced with an equimolar amount of methyl methacrylate (MMA), while keeping all other conditions the same, to verify the effect of the benzene ring structure on the interfacial interaction between the dispersant and the inorganic particles.
[0052] Comparative Example 5 The monomer molar ratio in Example 1 was adjusted to: IA:BzMA:HPMA = 0.3:1:1.7 to verify the rationality of the monomer ratio range in the claims.
[0053] Comparative Example 6: Molecular Weight Adjustment The monomer ratio was the same as in Example 1, but the amount of chain transfer agent dodecyl mercaptan was increased to 2.0 g to obtain a low molecular weight copolymer.
[0054] This comparative example is used to verify the effect of weight-average molecular weight below 5000 g / mol on thermal storage stability.
[0055] Performance testing (1) The weight-average molecular weight Mw of the copolymer dispersants obtained in the examples and comparative examples was determined by gel permeation chromatography. The results are shown in Table 1.
[0056] (2) The dispersion effect of the copolymer dispersants obtained in the examples and comparative examples was evaluated as follows: Dispersion system composition: Electronic grade barium titanate powder (BaTiO3) was selected, with an initial median particle size (D) of [missing information]. 50 Its thickness is 0.20 μm, and its specific surface area is 8~10 m². 2 / g.
[0057] Slurry preparation formula: Barium titanate powder: 65 wt%; Solvent: Butanone (MEK) and ethanol mixed at a mass ratio of 1:1; Dispersant addition: Copolymer dispersant solids account for 1.5 wt% of the mass of barium titanate; Dispersion process: Dispersion is carried out using a planetary ball mill with zirconia balls ( 0.5 mm), ball-to-material ratio 2:1, rotation speed 800 rpm, dispersion time 2 h.
[0058] The viscosity test method was as follows: a rotational viscometer was used to measure the viscosity at 25°C and a shear rate of 100 rpm. Particle size testing method: The particle size distribution of the slurry was tested using a laser particle size analyzer, and the initial particle size (tested immediately after dispersion) and the particle size after heat storage (tested after heat storage treatment) were recorded respectively. Thermal storage stability test: The prepared slurry was sealed and stored in a 60℃ constant temperature box for 7 days. After being taken out and restored to room temperature, the viscosity and particle size changes were tested.
[0059] (3) Ash content test: The dispersant to be tested was dried at 105℃ to constant weight. About 2.0g of the dried sample was weighed and placed in a platinum crucible that had been treated to constant weight. It was first carbonized at low temperature on an electric furnace, and then placed in a muffle furnace and burned at 750℃ for 2h. After cooling to room temperature, it was weighed and the ash content was calculated according to the ratio of the mass of the residue to the mass of the dried sample.
[0060] (4) Metal ion content test: Weigh about 0.5g of dried sample, add analytical grade nitric acid and hydrogen peroxide for microwave digestion, and after the digestion solution is brought to a final volume, test the Na content using ICP-MS. + K + and Li + Content; the detection limit for each ion was 0.5 mg / kg. The results of ash content and metal ion content tests are shown in Table 2.
[0061] The viscosity, particle size, and thermal storage stability test results obtained from the examples and comparative examples are shown in Table 1.
[0062] Table 1. Test results of viscosity, particle size, and thermal storage stability obtained from the examples and comparative examples.
[0063] Table 2. Test results of ash content and metal ion content obtained from the examples and comparative examples.
[0064] The following conclusions can be drawn from Tables 1 and 2: ① Comparison of initial dispersion ability: Examples 1-3 all showed better dispersion performance than Comparative Example 1 (SMA system), with significantly smaller initial particle size, indicating that the present invention effectively improves the wetting and adsorption capacity of the dispersant in polar systems by introducing hydroxypropyl ester side chains and benzene ring structures. Comparative Example 5, due to its low itaconic acid content and insufficient anchoring groups, resulted in weak adsorption on the particle surface, leading to significant coarsening of the system during storage (viscosity increase rate >20% after 7 days).
[0065] ② Differences in thermal storage stability: In Example 1, after thermal storage, D 50 The D value increased only from 0.22 μm to 0.23 μm. 90 The minimal changes indicate the formation of a stable steric hindrance layer and adsorption layer. In Example 3, due to the increased proportion of hydroxypropyl ester, the initial viscosity was lower, but the relative density of anchoring groups and aromatic adsorption units decreased, resulting in a slight increase in particle size after heat storage. In Comparative Example 3 (HEMA substitution), due to the shorter side chains and insufficient steric hindrance layer, the particle size increased significantly after heat storage, indicating that the side chain length of HPMA and the synergistic effect of the ternary ratio have a significant impact on long-term stability.
[0066] ③ Influence of molecular weight: In Comparative Example 6, due to its low molecular weight, D... 90 The molecular chain length increased significantly from 0.65 μm to 1.10 μm, verifying the key role of molecular chain length in the formation of the spatially stable layer.
[0067] ④ Effect of structural substitution: The viscosity of the dispersant obtained in Comparative Example 3 (HEMA substitute) decreased slightly during the initial dispersion process, but the viscosity growth rate increased significantly (+18%) after 7 days of thermal storage, and D 90 The significant increase in particle size indicates that shorter side chains cannot form an effective steric hindrance layer, leading to decreased system stability. The dispersant obtained in Comparative Example 4 (MMA substitute) lacks an aromatic ring structure, resulting in decreased particle adsorption capacity and a significant increase in particle size, suggesting that benzyl methacrylate plays a crucial role in interfacial interactions.
[0068] ⑤ Zero ion contamination advantage: Although the initial dispersion effect of Comparative Example 2 was close to that of Example 1, it contained Na + The presence of metal ions makes it unsuitable for high-end electronic material systems; this invention achieves the elimination of metal ions while maintaining dispersion performance, offering significant application advantages. Table 2 shows that the ash content of Examples 1-3 is ≤0.015 wt%, and the Na content is... + K + and Li + All were below 0.5 mg / kg; while the Na in Comparative Example 2 was below 0.5 mg / kg. + The content reaches 23,500 mg / kg, indicating that the present invention can simultaneously achieve dispersion stability and low metal ion pollution control.
[0069] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A terpolymer dispersant with zero alkali metal ion pollution, characterized in that, It is obtained by copolymerization of itaconic acid monomer, benzyl methacrylate monomer and hydroxypropyl methacrylate monomer under the action of an initiator; The molar ratio of itaconic acid monomer, benzyl methacrylate monomer, and hydroxypropyl methacrylate monomer is (1.0~2.0):(1.0~3.0):(0.5~1.5). The weight-average molecular weight of the zero-alkali metal ion contamination terpolymer dispersant is 5000~15000 g / mol.
2. The terpolymer dispersant with zero alkali metal ion contamination according to claim 1, characterized in that, The zero-alkali metal ion contamination terpolymer dispersant has a molecular weight distribution index of 1.5~2.5, and its ash content, calculated as solids of the terpolymer dispersant, is ≤0.05 wt%, with Na... + Content ≤1.0 mg / kg, K + Content ≤1.0 mg / kg.
3. The terpolymer dispersant with zero alkali metal ion contamination according to claim 1, characterized in that, The zero-alkali metal ion contamination terpolymer dispersant exists in the form of free acid or organic amine salt.
4. The terpolymer dispersant with zero alkali metal ion contamination according to claim 1, characterized in that, The initiator includes an organic peroxide or an azo initiator, wherein the organic peroxide or azo initiator does not contain alkali metal or alkaline earth metal ions.
5. A method for preparing the terpolymer dispersant with zero alkali metal ion contamination as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Benzyl methacrylate and hydroxypropyl methacrylate were mixed to obtain a monomer mixture; Itaconic acid, organic solvent and chain transfer agent are mixed to obtain the reaction precursor solution; The precursor solution is heated to the polymerization reaction temperature, and the monomer mixture and the first initiator solution are added dropwise simultaneously. The polymerization reaction is carried out simultaneously during the dropwise addition to obtain the polymerization reaction solution. A second initiator is added to the polymerization reaction solution to carry out a aging reaction, thereby obtaining a terpolymer dispersant with zero alkali metal ion contamination.
6. The preparation method according to claim 5, characterized in that, The chain transfer agent includes one or more of dodecyl mercaptan, mercaptoethanol, isooctyl mercaptoacetate, isooctyl 3-mercaptopropionate, tert-dodecyl mercaptan, and n-octyl mercaptan. The chain transfer agent accounts for 0.05 to 0.8% of the total monomer mass.
7. The preparation method according to claim 5, characterized in that, The mass of the first initiator is 0.5% to 1.5% of the total monomer mass; The mass of the second initiator is 0.05 to 0.5% of the total monomer mass.
8. The preparation method according to claim 5, characterized in that, The polymerization reaction is carried out at a temperature of 75-85°C, and the monomer mixture and the first initiator solution are added simultaneously over a period of 2-4 hours.
9. The preparation method according to claim 5, characterized in that, The ripening reaction is carried out at a temperature of 85-95°C for 2-4 hours.
10. The application of the zero-alkali metal ion contamination terpolymer dispersant according to any one of claims 1 to 4 or the zero-alkali metal ion contamination terpolymer dispersant prepared by the preparation method according to any one of claims 5 to 9 in electronic pastes.
Citation Information
Patent Citations
Multipolymer surfactant and preparing technology thereof
CN106582438A
Aqueous hydroxy acrylic resin secondary dispersion
CN120888031A